KAJIAN PENGARUH KOMPETENSI KEPRIBADIAN DAN SOSIAL TERHADAP KINERJA GURU - Iskandar Agung (Jurnal Ilmiah Visi, 2014)
Effort to improve the outcomes of student learning quality is very depend on the possession of competencies that make up the professionalism of teachers. Among the components of competence, that is personal competence and social competence, which is thought to have a significant influence on the teacher performance of the duties/work. The present study is focus on high school teacher. Both of these competencies are exogenous variables that proved to be a positive influence on the performance of the teacher as an endogenous variable. From the data processing is also obtained, that the number of indicators at the top rank in contributing to the exogenous variables studied are the Competence of Personality and Social Competence. Rank of indicators in personal competence are leadership, work ethic, self-sustainable development, and achievement orientation; rank of indicators in social competence is an communicative, objective, nondiscriminativey, and authority. The results of this study should receive special attention and consideration by the authorities in the process of establishing and improving the competence of teachers, both in the PLPG,PPG Dalam Jabatan, PPG Prajabatan, and teacher education by LPTK.